Antimicrobial resistance and mechanisms of epigenetic regulation - Wang, Xinrui; Yu, Donghong; Chen, Lu (Frontiers in Cellular and Infection Microbiology, 2023)
The rampant use of antibiotics in animal husbandry, farming and clinical disease treatment has led to a significant issue with pathogen resistance worldwide over the past decades. The classical mechanisms of resistance typically investigate antimicrobial resistance resulting from natural resistance, mutation, gene transfer and other processes. However, the emergence and development of bacterial resistance cannot be fully explained from a genetic and biochemical standpoint. Evolution necessitates phenotypic variation, selection, and inheritance. There are indications that epigenetic modifications also play a role in antimicrobial resistance. This review will specifically focus on the effects of DNA modification, histone modification, rRNA methylation and the regulation of non-coding RNAs expression on antimicrobial resistance. In particular, we highlight critical work that how DNA methyltransferases and non-coding RNAs act as transcriptional regulators that allow bacteria to rapidly adapt to environmental changes and control their gene expressions to resist antibiotic stress. Additionally, it will delve into how Nucleolar-associated proteins in bacteria perform histone functions akin to eukaryotes. Epigenetics, a non-classical regulatory mechanism of bacterial resistance, may offer new avenues for antibiotic target selection and the development of novel antibiotics.